2021
DOI: 10.1002/qua.26850
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the effect of Vx doped LaFe1−xO3 for advanced optical, spintronic, and thermoelectric devices

Abstract: In this theoretical work, we perform an investigation to study the influence of V doping in LaFeO 3 (LFO). For V doping, the opted Fe site shows remarkable modifications in the inherited attributes of pristine LFO. We use formation energies and optimizations to explore the ground state structural stability. Electronic properties of stable structures reveal large spin polarization effects with spin-up (metallic) and spin-down (semiconducting) configurations. We observe the highest ferromagnetism for V-25% dopin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…All compounds have shown a mechanical stability for the cubic phase. The strength of materials can be estimated using moduli of elasticity, which have been estimated using well defined mathematical relations such as bulk modulus B , C 2C 3 11 12  = is used, which C 0  > indicates the majority of bonds exhibit ionic bonding while for C 0  < majority bonds are covalent. All studied compounds indicate a predominant ionic nature.…”
Section: Mechanical and Thermal Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…All compounds have shown a mechanical stability for the cubic phase. The strength of materials can be estimated using moduli of elasticity, which have been estimated using well defined mathematical relations such as bulk modulus B , C 2C 3 11 12  = is used, which C 0  > indicates the majority of bonds exhibit ionic bonding while for C 0  < majority bonds are covalent. All studied compounds indicate a predominant ionic nature.…”
Section: Mechanical and Thermal Propertiesmentioning
confidence: 99%
“…These compounds have been extensively studied due to novel applications in power generation, fuel cells, spintronics, actuators, magnetic sensors, super-strong composite alloys, supercapacitors, high-pressure optical and magnetic sensors, piezoelectric sensors, and radiation tracers [1][2][3]. Through experiments and theoretical findings, it has been found that most of the aforementioned applications are found in those perovskites that exhibit a multiferroic nature [4][5][6][7] and have a wide band gap of 1.5-3.0 eV, thus serving as good absorbers for solar cells and photochemical applications [8][9][10][11]. Moreover, some of the perovskite compounds have a halfmetallic nature, which allows for their use in useful optical applications in different energy ranges [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…9,16 Orthorhombically distorted LFO-perovskite was found to have multiferroic properties and has potential applications as a spin lter in spintronics. 17,18 It has been observed that 3d cations on the B-site (i.e., Mn 4+ or Fe 3+ ) of the crystal lattice drive the electrical and magnetic properties of LMO and LFO. The double exchange mechanism (DE) and the Jahn-Teller effect are the two main reasons for the co-existence of two ferroic orders in LMO and LFO ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…9,16 Orthorhombically distorted LFO-perovskite was found to have multiferroic properties and has potential applications as a spin filter in spintronics. 17,18…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and theoretical studies reported that perovskites have been of interest in the majority of the aforementioned applications which demonstrate their multiferroic characteristics 4–7 . Moreover, owing to their 1.5–3.0 eV broad energy band gap, these perovskites exhibit excellent absorption properties for employment in solar cell and photochemical applications 8–11 …”
Section: Introductionmentioning
confidence: 99%